Răspuns :
[tex]( {2}^{1999} - {2}^{1998} - {2}^{1997} ) \div {4}^{998} [/tex]
[tex] = [ {2}^{1997}( {2}^{2} - 2 - 1) ] \div { ({2}^{2} )}^{998} [/tex]
[tex] = [ {2}^{1997} (4 - 2 - 1)] \div {2}^{2\times998} [/tex]
[tex] = ( {2}^{1997} \times 1) \div {2}^{1996} [/tex]
[tex] = {2}^{1997} \div {2}^{1996} [/tex]
[tex] = {2}^{1997 - 1996} [/tex]
[tex] = {2}^{1} [/tex]
[tex] = 2[/tex]
[tex] = [ {2}^{1997}( {2}^{2} - 2 - 1) ] \div { ({2}^{2} )}^{998} [/tex]
[tex] = [ {2}^{1997} (4 - 2 - 1)] \div {2}^{2\times998} [/tex]
[tex] = ( {2}^{1997} \times 1) \div {2}^{1996} [/tex]
[tex] = {2}^{1997} \div {2}^{1996} [/tex]
[tex] = {2}^{1997 - 1996} [/tex]
[tex] = {2}^{1} [/tex]
[tex] = 2[/tex]
[tex]2^{1999}-2^{1998}-2^{1997}:4^{998} =\\ \\ 2^{1997}(2^{2} -2^{1} -1):(2^{2})^{998}=\\ \\ 2^{1997}(4-2-1):2^{1996} =\\ \\ 2^{1997}:2^{1996}=2^{1997-1996} \\ \\ =2^{1}\\ \\ =2[/tex]